PRAKTEK HUKUM PENENTUAN GANTI RUGI OLEH HAKIM SEBAGAI AKIBAT ADANYA GUGATAN WANPRESTASI PADA KASUS HUTANG PIUTANG ATAU TUNTUTAN MEMBAYAR SEJUMLAH UANG DI PENGADILAN NEGERI SURAKARTA - Th. Wahyu Winarto; Hari Purwadi; Widodo T Novianto (Program Pascasarjana Fakultas Hukum Universitas Sebelas Maret Surakarta, 2017)
AbstractThis article aims to know the components and standards what is used and what legal practice used by judge District Court of Surakarta to determine punitive damages based on tort lawsuits in the dispute a debt receivable or pay an amount of money. The article is the juridical normative research. That the practice of law determining the indemnity by the judge as a result of any such tort lawsuits in case of debts receivable or demands payment of a sum of money in the District Court of Surakarta, that conclusion can be obtained in determining his little big compensation is required, the judge uses standard components and such indemnity as provided for in Article 1243 until 1252 The Book Of Civil Law (KUHPerdata) and the law is rooted in the jurisprudence. So that legal considerations in the verdict, a very dry atmosphere of juridical, sociological and philosophical. Recommendation in the context of the discovery of the law by the judge, in order to provide authoritative legal verdict, then required the preparation of material different methods of determining the law regarding the determination of the damages, and legal discovery method as a reference for judges in carrying out tasks mandated laws.Keywords : Indemnity, Tort Lawsuit, Debt Receivable AbstrakArtikel ini bertujuan untuk mengetahui komponen-komponen dan standar apa yang dipakai dan apa Praktek hukum yang dipakai oleh hakim Pengadilan Negeri Surakarta untuk menentukan ganti rugi yang didasarkan pada gugatan wanprestasi dalam sengketa hutang piutang atau tuntutan membayar sejumlah uang. Artikel ini adalah penelitian yuridis normatif. Dalam menentukan besar kecilnya ganti rugi yang dituntut, hakim menggunakan komponen dan standar ganti rugi seperti seperti yang diatur dalam Pasal 1243 sampai dengan 1252 KUHPerdata dan hukum yang digunakan adalah yang dianut dalam yurisprudensi. Sehingga pertimbangan-pertimbangan hukum dalam putusan tersebut, sangat kering oleh hakim, agar dapat menghasilkan putusan hukum yang berwibawa, maka diperlukan penyusunan materi berbagai metode penentuan hukum mengenai Praktek penentuan ganti rugi, dan sekaligus metode penemuan hukum sebagai acuan bagi para hakim dalam menjalankan tugas yang diamanatkan undang-undang. Kata Kunci : Ganti Rugi, Gugatan Wanprestasi, Hutang Piutang